Lymphatic drainage on healthy and neoplasic mammary glands in female dogs: Can it really be altered? - Pereira, C. T.; Rahal, S. C.; Balieiro, JCD; Ribeiro, AACM (Blackwell Verlag Gmbh, 2003)
The purpose of this research was to study the mammary lymphatic drainage under a macroscopic and mesoscopic view, comparing the vascular pattern of healthy and neoplasic mammary glands injected with drawing ink alcoholic and fluorescein solutions, in 46 mongrel female dogs. The results pointed out that the thoracic gland is drained by the axillary lymph centre, but in mammary neoplasia either superficial cervical or ventral thoracic lymph centres can be involved. Cranial and caudal abdominal glands may be drained by the axillary, inguinofemoral and popliteal lymph centres. However, the popliteal drainage is specific for the healthy caudal abdominal mammary gland. The inguinal gland can be drained by both inguinofemoral and popliteal lymph centres in both neoplasic and healthy conditions. Regarding the mammary lymphatic communications, this research demonstrated that neoplasic glands present more types of anastomosis (40.9%), than healthy glands (33.33%), and an increase in contralateral anastomosis (50%) compared with healthy ones (33%). Given the data, the mammary neoplasia can change the lymphatic drainage pattern in terms of lymph centres and vascular arborization, thus forming new drainage channels and recruiting a larger number of lymph nodes. Lastly, some comments were made about the severity of a specific neoplasic mammary gland and conditions to be considered before making a decision in terms of the most adequate operative procedure, and suggestions for further investigations.